Prototype testing in product development: the case of the Nano Membrane Toilet. - Hennings, Jan (Cranfield University, 2020)
The provision of safely managed sanitation in densely populated urban settlements of cities in low- and middle-income countries poses complex challenges. To address these challenges, Cranfield University is developing the Nano Membrane Toilet, a novel standalone household-level sanitation technology that operates off the grid and safely treats human waste while having an aspirational design. Developing such a complex novel product requires testing a multitude of prototypes in numerous ways. Since designing, building and testing the prototypes is often done by separate teams of various disciplines, the entire testing process requires a considerable amount of planning and communication. This thesis not only reports on field trials and laboratory testing of two prototypes of the Nano Membrane Toilet, but also investigates the under-explored field of planning and communicating prototype tests for complex product development processes. In a first trial, a prototype mechanical toilet flush is assessed in user tests and lab tests. It is shown to be liked by users of Urine Diversion Dehydration Toilets, and it appears to perform best when lubricated and with a silicone rubber with oil-bleed-effect for its swipe. A second round of tests explores settling and displacement as means of solid-liquid separation in the Toilets collection tank. Toilet paper is shown to inhibit settling of faeces, while a conical tank geometry promotes it. From a literature review and subsequent interviews with experts in prototype testing, a visual tool for planning and communication prototype tests for the Nano Membrane Toilet is developed, validated and refined into a generally applicable, modular version. This modular tool can be used to produce customised visual testing strategies for a variety of product development processes, to facilitate planning and communicating testing activities across interdisciplinary teams.
Keywords: Sanitation; reinvent the toilet challenge; interdisciplinary communication; complex product development processes; toilet paper; conical tank geometry